Conflict of interest in the workplace and its consequences - Ali Mohamed, Ashgar Ali (Malaysian Institute of Management (MIM), 2017)
The employment relationship is a fiduciary one where the core obligation is one of loyalty and integrity — the key characteristics an employee should possess, no matter what form of employment he is engaged in (see, Kvaerner Petrominco Engineering Sdn Bhd v Virginia Jaqueline Chan [2007] 1 ILR 494). It includes, the employee’s obligation to act in good faith; not to make profit out of his trust; not to place himself in a position where his duty and his interests may conflict; not to act for his own benefit or the benefit of a third party without the informed consent of his employer; and not to misuse the employer’s confidential information for his own benefit. Further, it is an implied term that the employee will serve the employer in good faith. In turn, the employer places confidence and trust in the employee and this includes trusting the company’s property in their care. The employee should not betray the trust and confidence reposed on him by the company. An employee who defrauds the company by falsifying and manipulating the company’s documents and divulging the company’s business information to a third party without prior approval or authorisation from the company, amongst others, would be committing acts of a grievous nature (see, Normalina Mansor v MSU Holdings Sdn Bhd [2017] 3 ILR 183 and Ho Khoy Li v KS Lau & Co [2016] 2 ILR 586). The integrity of the employee in the aforesaid circumstances would be seriously jeopardised as he would have breached the very foundation of his contract of employment. It would be difficult for any employer to repose trust and confidence in the said employee thereafter. An essential component of the employee’s duty of fidelity is the obligation to serve in the best interest of the employer. An employee should not place himself in a position where his interests conflict with his duties. As aptly noted by the Industrial Court in Esso Production Malaysia Incorporated v Md Yusof Nordin [1997] 2 ILR 711, ‘the employee is required at all times, to act in a faithful manner and not to place himself in a position where his interests conflict with his duties.’ It would be a clear violation of the duty of fidelity when an employee acts in conflict with the best interest of the employer for example, conducting private business during working hours, stealing the employer’s customers, or supplying the company’s business information to the company’s competitor. In Pantas Cerah Sdn Bhd v Lau Boon Seng [1999] 3 ILR 216, the Industrial Court stated inter alia, that: ... it is implied that the employee will faithfully with loyalty and honesty further the interest of the employer. There is a fiduciary relationship between the employer and the employee. An employee, under the payroll of the employer should not do any act which causes detriment to the interest of the employer It is noteworthy that an employee who has committed wrongdoings inconsistent with the employer-employee relationship would be deemed to have betrayed the trust and confidence reposed on him. In such circumstances, it would be unsafe to continue his employment and this would justify immediate dismissal. Having said the above, the consequences ensuing from workplace conflict of interest is discussed in this article with reference to the awards by the Industrial Court.